Mengeksplorasi Motivasi Perempuan di Desa Purwoharjo untuk Berwirausaha - Prasetyo, Tri Utomo; Transistari, Ralina; Wahyuningsih, Tri Harsini; Suparmono, Suparmono (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to explore the motivation of women in Desa Purwoharjo, Kabupaten Kulon Progo to become entrepreneurs. The method used is a mixed method. A total of 26 informants were involved in this study through snowball sampling. Data were collected through semi-structured interviews. A qualitative approach with the content analysis method was used to analyze the reasons that motivate women in Desa Purwoharjo to become entrepreneurs. A quantitative approach with the Fisher's Exact test and One-way Anova was used to analyze the relationship between entrepreneurial motivation and sociodemographic factors. The results of the study showed that the main reasons that motivate entrepreneurship are (1) increasing family income, (2) earning your own income, and (3) utilizing free time. The dominating reason for “increasing family income” shows that informants became entrepreneurs with the motive of fulfilling their physiological needs. Only a few informants have achieved the provision of social needs and appreciation. The absence of informants who mentioned the reason for